2019
DOI: 10.1021/acsphotonics.9b00219
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Concatenation of 1.5 fs Pulses in the Deep Ultraviolet

Abstract: Laser pulses with a duration of one femtosecond or shorter can be generated both in the visible-infrared (Vis-IR) and in the extreme UV, but the deep UV is a spectral region where such extremely short pulses have not yet been demonstrated. Here, a method for the synthesis of ultrashort pulses in the deep UV is demonstrated, which utilizes the temporal and spatial harmonics that are generated by two noncollinear Vis-IR pulses in a thin MgF2 plate. By controlling the groove-envelope phase of the Vis-IR pulses, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…2b). As previous studies 23,24 revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [23][24][25] .…”
Section: Data Evaluationmentioning
confidence: 64%
See 1 more Smart Citation
“…2b). As previous studies 23,24 revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [23][24][25] .…”
Section: Data Evaluationmentioning
confidence: 64%
“…As previous studies 23,24 revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [23][24][25] . V is beneficial for the interpretation of the data because it is generated within the first few micrometers and maintains its spectrum in the subsequent linear propagation.…”
Section: Data Evaluationmentioning
confidence: 64%
“…2 b). As previous studies [22,23] revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [22][23][24].…”
mentioning
confidence: 64%
“…As previous studies [22,23] revealed, the spectral fringes are produced by two DUV pulses that are well separated in time after the crystal. The leading pulse (labeled U) is in time with the Vis-IR pulse, whereas the trailing pulse (labeled V) propagates at the DUV group velocity [22][23][24]. V is beneficial for the interpretation of the data, because it is generated within the first few micrometers and maintains its spectrum in the subsequent linear propagation.…”
mentioning
confidence: 64%
“…The pulse retrieval is analytic, and the fidelity can be checked by comparing the complex-valued data trace with the retrieved trace. Originally demonstrated for the retrieval of two pulses in the deep ultraviolet, which are scanned with a further unknown NIR pulse [29], the method is here applied for three unknown frequency-degenerate pulses U, V and W using the variant center of the original publication [21].…”
Section: Pulse Retrievalmentioning
confidence: 99%